Innovative managerial principles for enhancing teacher performance and student learning outcomes - Corry Yohana; Faerozh bin Madli; Annisa Lutfia; Ratna Tri Hari Safariningsih; Nurdin Hidayat; Eva Catherin Agustine; Salsa Delina (Kurdish Studies, 2024)
Principal is known to posses a strategic role in designing an environment for the development and implementation of innovations in improving the quality of education. In order to better teachers' performance and student learning outcomes at the Elementary to High School or Vocational School levels in Jabodetabek, this study set out to examine the effects of the factors of critical thinking, collaboration, vision, emotional intelligence, and the school environment on principal managerial creativity. A total of 200 teachers were recruited as respondents and determined by the convenience sampling technique. Furthermore, the determination of the sample size was in line the formula devised by Krejcie and Morgan. Data collection was also carried out through online discussions and distributing questionnaires to respondents. The Mix method approach (a combination of quantitative and qualitative) was used and data analysis was performed using AMOS. The results showed that critical thinking, school vision, emotional intelligence, and the school environment had a positive influence on principal managerial creativity. In addition, the positive influence of principal managerial creativity on teacher performance and student learning outcomes was validated.